Responsiveness of Local Villages in the Implementation of COVID-19 Protocols in the Philippines - Steve-Pj Carpio; Charliedel Dela Cruz; Gianella Saquing; Darin Jan Tindowen (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was conducted to examine the responsiveness of barangays to the implementation of IATF protocols. By utilizing mixed methods research design, the study achieved its objectives by employing a modified questionnaire that determines the responsiveness of five barangays in Tuguegarao City, Cagayan. Moreover, the study involved 250 local residents and 50 barangay officials who both willingly participated in the data gathering. For the data analysis, descriptive quantitative and thematic analysis were used. The results revealed that both perceived their respective barangays to be responsive in the implementation of IATF protocols. Results also portrayed a significant difference between the assessment of barangay officials and local residents. In addition, it was also found that there’s a significant difference in the assessment of barangay officials and residents when grouped according to barangay profile. It was also revealed that despite the responsiveness, there were still issues and challenges that both barangay officials and residents experienced in implementing IATF protocols in their barangays.